Hemoperitoneum from ruptured liver tumors: About 9 cases - Praderi, José; Estefan, Alberto; Piñeyro, Alberto; Armand Ugón, Alfredo; D'Auria, Agustín; Falchetti, Juan C. (Cirugía del Uruguay, 1986)
The more frequent causes of spontaneous hemoperitoneum in male are: rupture ol abdominal aortlc collaterals or solid organs as liver or spleen. This complication is more frequently seen in pathologic liver. The authors have presentad 9 cases, 7 of same died in the acute period. This is a practically fatal Complication that is diagnosed by clinical and auxiliary procedures (paracentesis and fiberoptic laparoscopy).